Exploring the forest--poverty link: key concepts, issues and research implications - Angelsen, A.; Wunder, Sven (Center for International Forestry Research, 2003)
This paper provides a global review of the link from forests to poverty alleviation. Definitions are clarified and the key concepts and indicators related to livelihoods and policy reduction and prevention are explored--distinguishing between the analysis and the measurements of poverty. Reviewing the macro-level literature on the relationship between economic growth, inequality and poverty, the authors found that economic growth usually does trickle down to the poor and that poverty reduction without growth is in practice very difficult to achieve. The potentials and limitations of forests in regard to poverty allevition are canvassed and their possible roles as safety nets, poverty traps and pathways out of poverty are explored. The core discussion addresses how forests can contribute to poverty reduction, distinguishing three main benefit categories. Firstly, non-timber forest products serve subsistence needs, may have important gap filling or safety net functions. Secondly, timber has not traditionally been very pro-poor but the current trends of increased local ownership of natural forests, growing tree commercialisation and small scale wood processing could modify that picture. Thirdly, ecological service payments are emerging rapidly but it is uncertain how much the poor will benefit. In conclusion, this paper outlines ten promising research topics, within three broader fields: assessing current forest-based benefits to the poor; exploring emerging market opportunities; and evaluating cross-cutting institutional and extra-sectoral issues.